2007
DOI: 10.1002/num.20305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ODE methods for laminar reacting gas flow simulations

Abstract: Two-dimensional transient simulations are presented of the transport phenomena and multispecies, multireaction chemistry in chemical vapor deposition (CVD). The transient simulations are run until steady state, such that the steady state can be validated against the steady state solutions from literature. We compare various time integration methods in terms of efficiency and robustness. Besides stability, which is important due to the stiffness of the problem, preservation of non-negativity is crucial. It appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In [18] we have shown that careful numerical analysis results in successful determination of time accurate solutions. However, in [18] we did not discuss efficient linear solvers. This is one of the topics of this paper.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…In [18] we have shown that careful numerical analysis results in successful determination of time accurate solutions. However, in [18] we did not discuss efficient linear solvers. This is one of the topics of this paper.…”
Section: Introductionmentioning
confidence: 96%
“…doi:10.1016/j.jcp.2009. 11.004 details are given in Section 4 of this paper and in [18]. Under these circumstances most of the computing work is consumed by solving the system of Eq.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations